Scanning Electron Microscopic Studies of Candida albicans - Barnes, W. G. (1971)
A scanning electron microscopic study of selected morphological stages of Candida albicans is presented. Stages represented are budding yeast cells, mycelial-like forms, chlamydospores, germ tube formation, and an unusual rough cell type.